Relevance of histamine and tryptase concentrations in nasal secretions after nasal challenges with phosphate buffered saline and allergen - D. Wang; P. Clement; J. Smitz; M.-P. Derde (Mediators of Inflammation)
In this prospective study, a quantitative determination of histamine and tryptase in nasal secretions after nasal phosphate buffered saline (PBS) and allergen challenge was performed in 18 atopic patients who were compared with ten non-allergic healthy volunteers. The aim of the study was to determine the normal and pathological concentrations of these important mediators in nasal secretions. The second objective was to test the relevance of these two mast cell secreted mediators after nasal challenge. Results showed that the concentrations of tryptase in almost all samples were under the minimal detection limit (< 0.5 μU/g) and only a sigrtificant increase of tryptase (median, 28 μU/g) occurred immediately after nasal allergen challenge in the patient group. Histamine concentration significantly increased after every nasal PBS challenge (median, 69 ng/g after first PBS challenge and 165 ng/g after second PBS challenge) in the control group, as well as in the patient group after both PBS (median, 69 ng/g) and allergen (median, 214 ng/g) challenge. On the other hand, a rapid onset of sneezing and increase in nasal airway resistance was experienced only in the patient group after nasal allergen challenge, but did not occur after PBS challenge even though the histamine concentrations significantly increased in both groups. This study suggests that tryptase is a more preferable marker than histamine in quantitative monitoring of mast cell activation especially during the early phase nasal allergic reaction.